Development of a training model to improve the managerial competence of Islamic boarding schools based on problem-based learning - Yoga Amarta; Jasrial; Nurhizrah Gistituati; Ahmad Sabandi (Universitas Jambi, Indonesia, 2025)
This research aimed to develop a valid, practical, and effective problem-based learning-based managerial competency improvement training model for Islamic boarding school administrators. This research and development (R&D) research was developed using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The instruments were interview sheets, needs analysis questionnaires, validity questionnaires, practicality questionnaires, and test instruments. The results showed that the validity test of the developed training model was in the valid category, with an average score of 0.91. The average scores of the practicality test given by the instructor and training participants were 90.00% and 90.72%, respectively, in the efficient category. The results of training activities showed an increase in the average test score of 40.77 points, with a moderate increase criterion. The effectiveness test with the N-Gain formula scored 0.65, with a fairly effective category. Additionally, the conclusion was that the problem-based learning-based managerial competency improvement training model for Islamic boarding school administrators is valid, practical, and quite effective.